Socially Extended Cognition and Shared Intentionality - Lyre, Holger (Frontiers in Psychology, 2018)
The paper looks at the intersection of extended cognition and social cognition. The central claim is that the mechanisms of shared intentionality can equally be considered as coupling mechanisms of cognitive extension into the social domain. This claim will be demonstrated by investigating a detailed example of cooperative action, and it will be argued that such cases imply that socially extended cognition is not only about cognitive vehicles, but that content must additionally to be taken into account. It is finally outlined how social content externalism can in principle be grounded in socially extended cognition.